IMPROVING THE STUDENTS’ PRONUNCIATION ABILITY THROUGH NRT (NOTICING-REFORMULATION TASK) - Yasser Mallapiang (Universitas Muhammadiyah Makassar, 2015)
This research aimed at explaining the improvement of the students’ pronunciation ability in terms of English consonant dealing with fricative and affricative and English vowel dealing with front vowel and central vowel. To explain the improvement, the researcher used a Classroom Action Research (CAR) which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken at the eleventh grade students of SMK Negeri 1 Jeneponto with the number of the subject 28 students with 25 women and 3 men. Instruments are pronunciation/reading test and observation. The findings of the research were students’ improvement in English consonant of the English fricative consonant was 2.9 in data source (D-Test), 4.2 in cycle 1 and then, it became 6.4 in cycle 2 whereas in English affricative consonant was 3.0 in data source (D-Test), 4.2 in cycle 1 and then, it became 6.6 in cycle II. The students’ pronunciation ability of English front vowel was 3.3 in data source (D-Test), 4.6 in cycle 1 and then, it became 6.7 in cycle 2. English Central Vowel was 3.4 in data source (D-Test), 4.7 in cycle 1 and then, it became 6.8 in cycle 2.The students’ observation was 50.1 % in cycle 1 and it became 72.9 % in cycle 2. It means that NRT (Noticing-Reformulation Task)is one of the effective teaching strategies for the eleventh grade students at SMK Negeri 1 Jeneponto to improve their pronunciation ability.